COVID-19 DAN KONFLIK WARGA ADAT DALAM PEMBANGUNAN PARIWISATA DI DESA ADAT PERASI, KARANGASEM, BALI - Dewa Sumantra; Ketut Sukiani; I Nyoman Mardika (Universitas Warmadewa, 2022)
According to the WHO (World Health Organization), explained that the Corona virus is a virus that attacks the respiratory system and is more dangerous for people who have congenital diseases. The Corona virus initially appeared in China, more precisely in the city of Wuhan. The virus spread rapidly in various parts of the world and resulted in weakening international economic conditions and the tourism sector. One of the most felt impacts on the tourism sector can be seen from the level of guest visits which has decreased significantly. Therefore, it is necessary to have a SWOT analysis (Strength, Weekness, Opportunity, and Threat) which is carried out to find solutions so that tourist attractions can be developed during the COVID-19 pandemic. According to Utami (2019), SWOT analysis is a strategic planning technique that is useful for evaluating strengths ( strengths) and weaknesses (weaknesses), opportunities (opportunities), and threats (threats) in a project, both ongoing and in new planning. The benefits of SWOT for tourism objects are (1) as a strategy for determining the future in business continuity, (2) being used by stakeholders to determine the condition of internal and external factors of the company, (3) knowing the high level of market competition for your product or business, (Kartika , 2020). Apart from health issues, namely Covid-9. the study that tourism will prosper and improve the standard of human life where tourism is developed does not always materialize. It is evident from the real picture that tourism actually makes the people dispersed in the Perasi Traditional Village in the Pertima Dinas Village, Karangasem District, Karangasem Regency from 2009 to 2013. Klian Adat (customary leaders) because they do not agree with the contract land agreement process which is considered to be detrimental to the community. This small group fights for the land belonging to the traditional village (Laba pura) by fighting back so that the land belonging to the customary village is not confiscated by the bank because it was pledged by investors without a definite explanation. As a result of the attitude taken by the group called the Perasi Indigenous Village Unity Community Forum, they are marginalized in the Traditional Village because they have to accept the sanction of being ostracized (kesepekang).